2005
DOI: 10.1007/s10439-005-4698-y
|View full text |Cite
|
Sign up to set email alerts
|

3-D Nanomechanics of an Erythrocyte Junctional Complex in Equibiaxial and Anisotropic Deformations

Abstract: The erythrocyte membrane skeleton deforms constantly in circulation, but the mechanics of a junctional complex (JC) in the network is poorly understood. We previously proposed a 3-D mechanical model for a JC (Sung, L. A., and C. Vera. Protofilament and hexagon: A three-dimensional mechanical model for the junctional complex in the erythrocyte membrane skeleton. Ann Biomed Eng 31:1314-1326, 2003) and now developed a mathematical model to compute its equilibrium by dynamic relaxation. We simulated deformations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 38 publications
3
70
0
Order By: Relevance
“…Many proteins with functions to withstand mechanical stresses have modular architectures, i.e., they are composed of tandem-linked domains that are individually folded. The force-induced unfolding/refolding and deformation of these domains regulate the tensions in the protein molecules as required by the cellular processes, such as titin during muscle stretch (Granzier and Labeit 2004), fibronectin in the assembly and cell attachment of the extracellular matrix (Erickson 2002;Oberhauser et al 2002), and spectrin in the deformation of erythrocytes (Vera et al 2005). One common feature in the aforementioned biological processes is that they involve protein molecules in deformed or unfolded conformations.…”
Section: Biological Implications Of the Experimental Resultsmentioning
confidence: 99%
“…Many proteins with functions to withstand mechanical stresses have modular architectures, i.e., they are composed of tandem-linked domains that are individually folded. The force-induced unfolding/refolding and deformation of these domains regulate the tensions in the protein molecules as required by the cellular processes, such as titin during muscle stretch (Granzier and Labeit 2004), fibronectin in the assembly and cell attachment of the extracellular matrix (Erickson 2002;Oberhauser et al 2002), and spectrin in the deformation of erythrocytes (Vera et al 2005). One common feature in the aforementioned biological processes is that they involve protein molecules in deformed or unfolded conformations.…”
Section: Biological Implications Of the Experimental Resultsmentioning
confidence: 99%
“…Recently, other groups have found that the red blood cell membrane, which has a structure similar to that of the submembranous 'cortical' cytoskeleton of nucleated cells, can be effectively modeled as a tensegrity as well (Vera et al, 2005). On a smaller size scale, the geodesic nuclear lamina and mitotic spindle composed of microtubule struts that push out against a tensed mechanically continuous network of chromosomes and linked nuclear matrix scaffolds (Maniotis et al, 1997a) also have been described as prestressed tensegrity structures Pickett-Heaps et al, 1997).…”
Section: Tensegrity and Cellular Mechanotransductionmentioning
confidence: 99%
“…This model could then be used in studying RBCs with cytoskeletal defects which are typical in blood disorders such as hereditary spherocytosis and elliptocytosis (25,26). The present work thus seeks to provide a significant advance over previous models that were either formulated at the continuum scale (18), thereby ignoring the discrete cytoskeletal structure, or that assumed a fixed cytoskeleton connectivity (14,19,(27)(28)(29)(30), thereby useful only to study elastic cell deformation without any dynamic cytoskeletal remodeling due to mechanical, thermal, or chemical driving forces.…”
mentioning
confidence: 91%
“…The novelty of this model over prior spectrin-based simulations (14,19,(27)(28)(29)(30) is that the A-B association is breakable, as well as reformable, with the network topology changing dynamically. Under increasing tensile force, the A-B association breaks when their distance reaches the inflexion point of V AB (r), r inflexion ϭ (26/7) 1/6 , indicated as the red circle in Fig.…”
Section: Computational Modelmentioning
confidence: 99%